Consumption, Sustainability and Everyday Life - Hansen, Arve; Bo Nielsen, Kenneth (Consumption and Public Life, 2023)
This open access book seeks to understand why we consume as we do, how consumption changes, and why we keep consuming more and more, despite the visible damage we are doing to the planet. The chapters cover both the stubbornness of unsustainable consumption patterns in affluent societies and the drivers of rapidly increasing consumption in emerging economies. They focus on consumption patterns with the largest environmental footprints, including energy, housing, and mobility and engage in sophisticated ways with the theoretical frontiers of the field of consumption research, in particular on the 'practice turn' that has come to dominate the field in recent decades. This book maps out what we know about consumption, questions what we take for granted, and points us in new directions for better understanding-and changing-unsustainable consumption patterns.